A Comparative Study of Urinary Complication Rates before and after the Incorporation of a Urethral Lengthening Technique during Masculinizing Genital Gender Affirmation Surgery - Gupta, Richie; Gupta, Rajat; Puri, Anurag (Indian Journal of Plastic Surgery, 2022)
Objectives Masculinizing genital gender affirmation surgery (MgGAS) consists of operative procedures designed to help the transition of transmen in their journey toward male gender role. Phalloplasty and urethral lengthening remain the most challenging of these surgeries, as the female urethra (4 cm long) must be lengthened to male dimensions (15–29 cm) with anastomosis at two sites, the native urethra/pars fixa urethra and the pars fixa urethra-penile urethra. As a result, there is a high incidence of urinary complications such as strictures and fistulae. Authors incorporated a urethral lengthening technique to reduce urinary complications in MgGAS. They compare the rates of urinary complications rates in cohorts before and after the introduction of this technique.Materials and Methods Authors have been performing phalloplasty since past 27 years, utilizing mainly free radial artery forearm flap (fRAFFp 431 cases) and pedicled anterolateral thigh flap (pALTp 120 cases). A retrospective review and comparison of urinary complications were performed before and after the introduction of their new technique since March 2017.Results There was a statistically significant reduction in the incidence of stricture with and without fistulae (25.94% with conventional and 4.17% with urethral lengthening technique p = 0.001) and fistulae alone (12.81% with conventional and 2.78% with urethral lengthening technique p = 0.011) in fRAFFp cases. In pALTp cases, the respective reductions were 43.08 to 17.07%, p = 0.006 (significant), and 13.85 to 4.88%, p = 0.197 (not statistically significant).Conclusion Over years, the rates of urinary complications in MgGAS have remained constant, varying from 25 to 58% for strictures and 17 to 75% for fistulae as noted by many authors. Authors noted that in most of their cases, strictures occurred at distal pars fixa urethra (DPFU)-penile urethra anastomosis and incorporated a urethral lengthening technique, which lengthens the DPFU by 3 to 5 cm at this anastomotic site, thus significantly reducing the anastomotic tension and the rate of urinary complications.
Keywords: masculinizing genitoplasty; phalloplasty; gender incongruence; gender affirmation surgery; sex change surgery; forearm flap; anterolateral thigh flap; urethral stricture; urethral fistula